APPLICATION FOR SEARCHING HANGOUT PLACES BASED ON MIDDLE POINT OF PARTICIPANT’S LOCATION (MEEDLE) - Aprillia Kusumawardhani Pannita; Nur Hadisukmana (President University, 2020)
The lifestyle of the current year’s people is very different with the lifestyle of the people eight years ago. Start from the booming of Facebook as social media. It changes the ways of communicating. Those can be said that is the turning point of the digital era, from then the people are educated to share everything online and from those sharing it creates the opportunity to gather information that also affecting the change of conventional business process. Just one simple application can change the lifestyle of million people. From then, many other mobile application has help the simple task in our life.This work that developed an application named, Application for Searching Hangout Places Based on Middle Point of Participant’s Location ( MEEDLE ), will discuss the development of solving the simple problem of searching and deciding hangout place based on the data that internet shared. This application will give the user ease and effectiveness while using.